1974
DOI: 10.1159/000468114
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Metabolism in Depression: Clinical Application of the Probenecid Test1

Abstract: The MA hypotheses presume a relationship between disturbances in the central MA metabolism and the occurrence of depressive symptoms. One part of the MA hypotheses is the serotonin hypothesis, in which a relation is presumed between central serotonin deficiency and depression. The arguments in favour of this hypothesis are discussed, and particular attention is paid to data collected with the probenecid technique. The conclusion is, that there are depressions with and without serotonin deficiency and that thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The evidence that serotonin is profoundly involved in impulse control has been accumulating for a long time (van Praag and Korf, 1974;Robinson et al, 2008b). In the present study, we examined the effects of fluvoxamine, a selective serotonin reuptake inhibitor (SSRI), on impulsive-like action as assessed by the 3-CSRTT.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence that serotonin is profoundly involved in impulse control has been accumulating for a long time (van Praag and Korf, 1974;Robinson et al, 2008b). In the present study, we examined the effects of fluvoxamine, a selective serotonin reuptake inhibitor (SSRI), on impulsive-like action as assessed by the 3-CSRTT.…”
Section: Introductionmentioning
confidence: 99%
“…Some depressed pa tients seem to have a central deficiency of serotonin. In these patients, several studies showed a decreased baseline concentration of 5-HIAA [12] and a decreased 5-HIAA accu mulation after probenecid administration [13]. Probenecid inhibits transport of 5-HIAA from the central nervous system to the bloodstream.…”
Section: -Hydroxy-lndole-acetic Acid (5-hiaa) Studiesmentioning
confidence: 94%
“…Van Praag (l05) also conceives ofbimodality in the chemistry of depression, perhaps characterized by whether there is a central deficiency of 5HT or not (108). In therapeutic trials with clomipramine he found eight patients who did not respond.…”
Section: Serotoninmentioning
confidence: 99%